Inside the Virtuous Cycle between Productivity, Profitability, Investment and Corporate Growth: An Anatomy of China Industrialization - Xiaodan Yu; Giovanni Dosi; Marco Grazzi; Jiasu Lei (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This article explores the dynamics of market selection by investigating of the relationships linking productivity, profitability, investment and growth, based on China's manufacturing firm-level dataset over the period 1998-2007. First, we find that productivity variations, rather than relative levels, are the dominant productivity-related determinant of firm growth, and account for 15%-20% of the variance in firms' growth rates. The direct relation between profitability and firm growth is much weaker as it contributes for less than 5% to explain the different patterns of firm growth. On the other hand, the profitability-growth relationship is mediated via investment. Firm's contemporaneous and lagged profitabilities display positive and significant effect on the probability to report an investment spike, and, in turn, investment activity is related to higher firm growth.
Keywords: D22; L10; L20; L60; O30; 330